Óleos essenciais e monensina em suplementos múltiplos para bovinos de corte em pastejo no período das águas - Teobaldo, Ronyatta Weich (2018)
Cattle production systems in Brazil heavily rely on pasture as the main source of nutrients. However, the use of supplementation is often necessary to supply the limiting nutrients at each time of year. In addition, the use of feed additives with potential to act on manipulation of ruminal fermentation may improve nutrient utilization efficiency. The objective of this study was to evaluate the effects of the inclusion of a commercial blend of essential oils (composed of copaiba oil, cashew nut shell and castor oil) and monensin on nutritional parameters of grazing cattle (Urochloa brizantha cv. Marandu) with supplementation during the rainy season. Four rumen cannulated Nellore bulls (average BW of 374 ± 15.66 kg) were randomly distributed in a 4 x 4 Latin square, in one of four treatments: control (supplement without additive); monensin (control supplement with inclusion of monensin 20 mg/kg DM consumed); EO1 (Essential oil blend - control supplement with inclusion of blend of essential oils - 0.15 g/kg DM consumed]; EO2 (control supplement with inclusion of blend of essential oils - 0.30 g/kg DM consumed). The total experimental period lasted 76 days. Nutrient intake and digestibility, pH and ruminal ammonia-N, concentration and proportion of short chain fatty acids, efficiency of nitrogen utilization and microbial protein synthesis were evaluated. Dry matter intake, forage dry matter intake, crude protein intake and neutral detergent fibre intake were similar (P>0.05) for the lower dose of blend of essential oils (EO1) and monensin, and were higher (P>0.05) when compared to the higher blend dose of blend of essential oils (EO2) and control. Higher digestibility of the neutral detergent fibre was verified with the inclusion of EO1, as well as lower methane emissions when estimated by digestible organic matter. The inclusion of feed additives to the supplement altered no (P>0.05) ruminal pH, ruminal ammonia-N concentration and concentration and proportion of short chain fatty acids. It was verified by the dose-response analysis that the increase of the dose of the blend of essential oils provided a quadratic increase in the dry matter intake and neutral detergent fibre digestibility. The addition of the commercial blend of essential oils composed of copaiba oil, cashew nut oil and castor oil, at a dose of 0.15 g/kg DM consumed, and monensin improve ruminal fermentation for beef cattle fed grass pastures with supplementation on rainy season.